REKOMENDASI PENETAPAN KAWASAN EKOSISTEM ESENSIAL DI DESA PANJARATAN - Siti Qomariah; Gusti Muhammad Hatta; Abdi Fithria (Lambung Mangkurat University-Indonesia, 2021)
Essensial Ecosystem Areas in general can be interpreted as protected areas outside conservation areas. In Panjaratan Village, it is found an area that is a habitat for proboscis monkeys and other animals according to the results of the inventory but is outside the conservation forest area. The existence of proboscis monkey (Nasalis larvatus) habitat in Panjaratan Village needs to supported in conservation so that it does not experience extinction due to interference for human activities. This study aims to provide recommendations in planning the determination of essential ecosystem areas for the Nasalis larvatus habitat in Panjaratan Village. This research was qualitative by using an emic approach that focuses on data and analysis based on answers from key informant. The results showed that the presence of Nasalis larvatus habitat in Panjaratan Village received support from the community, government and the private sector in its empowerment activities. This is supported by the existence of an inventory and verification of the presence of Nasalis larvatus habitat in Panjaratan Village conducted by the South Kalimantan Natural Resource Conservation team and through identification activities to then propose the Nasalis larvatus habitat area in the village to become an area of essential ecosystem areas.